Intrahepatic Cholestasis of Pregnancy Between 34 Weeks And 40 WeeksWhen To Intervene - Yazdani, Tehreem; Imran, Ayesha; Amin, Nabila; Zaheer, Fareeha; Mukhtar, Saad; Yaqub, Umairah (Pakistan Armed Forces Medical Journal, 2022)
Objective: To find the appropriate timings for intervention in women with intrahepatic cholestasis of pregnancy.Study Design: Prospective observational study.Place and Duration of Study: Gynaecology and Obstetrics Department Combined Military Hospital Okara, from Oct 2019 to Nov 2020.Methodology: Patients between 34-40 weeks of gestation with intrahepatic cholestasis were included in the study. With clinical and biochemical findings patients were monitored and conventional treatment was given. Intervention by delivery was done when required. Maternal and fetal outcome were followed.Results: Out of 380 patients with pruritus between 34-40 weeks of gestation, intrahepatic cholestasis was found in 53 patients. Most of the patients 27 (51%) were delivered at 37-completed weeks. At 35-weeks of gestation 6 (11%) patients were delivered, at 36-weeks 8 (15%) patients were delivered, while 2% patients delivered at 39 and 40 weeks of gestation. The number of intrauterine deaths was 1 at 34 weeks of gestation and 2 at 35 weeks of gestation. Transient tachypnea of newborn was observed in 23% neonates. Respiratory Distress Syndrome was observed in 6 (12%) newborns. Neonatal sepsis was observed in 5 and hyperbilirubinaemia was observed in 4 (8%) neonates.Conclusion: Patients with intrahepatic cholestasis should be preferably delivered between 37 to 38 weeks for a better foetal outcome.